A COMPARATIVE STUDY OF SUBCUTANEOUS NODULES IN RHEUMATIC FEVER AND RHEUMATOID ARTHRITIS - Dawson, M. H. (The Rockefeller University Press, 1933)
The foregoing comparative study on the subcutaneous nodules in rheumatic fever and rheumatoid arthritis is presented as part of an investigation which has been conducted in this clinic on the relationship of the two clinical entities, rheumatic fever and rheumatoid arthritis. It is believed that the present study has shown that these lesions are highly characteristic of the two diseases and that they represent different phases of the same, fundamental, pathological process. However, it should be pointed out that the presence of closely related or even identical lesions in two, separate, clinical entities cannot be considered as valid evidence in support of the hypothesis that the two diseases are etiologically related. Comparative clinical studies on the relationship of rheumatic fever and rheumatoid arthritis will be presented in a succeeding communication. These studies, as well as serological investigations on the two diseases which have been reported elsewhere (23, 24), lend further support to the conception that rheumatic fever and rheumatoid arthritis are intimately related and possibly different responses of affected individuals to the same etiological agent.